Targeting the Adenosine‐Mediated Metabolic Immune Checkpoint with Engineered Probiotic for Enhanced Chemo‐Immunotherapy - Jinhui Wang; Jing Wang; Zhijie Yu; Hongyu Wen; Chensi Zhao; Jiayong Zhong; Chuanle Xiao; Yingqiu Li; Jianqiao Xu; Jinquan Wang; Zong‐Wan Mao; Wei Xia (Advanced Science)
Abstract Immunotherapy has revolutionized cancer treatment by leveraging the patient's immune system, yet its efficacy is often hampered by the immunosuppressive tumor microenvironment (TME). Adenosine, a key player in this milieu, suppresses immune cell activity via cAMP signaling. Here, an innovative strategy to remodel the TME using a genetically engineered strain of Escherichia coli Nissle 1917 that expresses adenosine deaminase on its surface under hypoxic conditions is presented. This engineered probiotic targets tumors, converts immunosuppressive adenosine to inosine, and enhances anti‐tumor immune responses. In vivo, the engineered probiotic significantly improved immune cell infiltration and demonstrated synergistic effects with low‐dose doxorubicin in both subcutaneous and orthotopic mouse colorectal cancer model. Furthermore, the engineered probiotic modulated the TME, promoting a shift from M2‐like to M1‐like macrophages and increasing effector T cell populations. These findings highlight the potential of using engineered probiotics for metabolic modulation of the TME, offering a novel approach for enhancing cancer immunotherapy.